Theology, Science, and Technology: Framing an Encounter in Light of Lonergan and Ricœur* - Pambrun, James R. (Horizons, 2015)
This article proposes a theological approach to the encounter between theology and the world of science and technology. A suitable locus for encounter is the different partners' shared commitment to the desire to understand. I draw on the work of both Bernard Lonergan and Paul Ricœur to describe understanding as the enactment of a pattern of cognitional operations. However, the theoretical mode of understanding proper to science is distinct from the practical mode of understanding proper to technology. Lonergan's elaboration of the "intellectual" pattern of operations is drawn on to enhance an encounter with science, while Ricœur's elaboration of the "action" pattern is drawn on to enhance an encounter with technology.